Pengaruh Advertising, Personal Selling dan Sales Promotion terhadap Keputusan Mahasiswa untuk Kuliah di STIKOM PROSIA - Sumirat, Pepen (Magister of Communication Science, Sahid University Jakarta., 2023)
This research aims at analyzing some of the influences of Advertising (X1), Personal Selling (X2), Sales Promotion (X3) as independent variables, either independently or individually concerning Decision for Lectures (Y) as the independent variables in STIKOM Prosia. The research uses a survey method with the application of the association as a result of using quantitative data, whereas the research describes the relationship between the dependent variable (Independent Decision and Sales Promotion) through the testing of the hypothesis. The questionnaire given to the respondent responders was made sideways by looking at the actual conditions behind the adoption of the second category of conditioning, personal selling, sales promotion, and institutional study. The data is collected in a conversation with weights that vary based on the response of the respondent for a valid test and reliability. testing of the prerequisite using a multiple correlations which aims to find the relationship between the two and the free variable (X) against the dependent variable (Y). The results of the study with the title of Affairs Advertising, Personal Selling, and Sales Promotion on the Decision for Lecture in STIKOM Prosia can be said to have a significant effect